Konsumsi Program Survival Show dan Pengaruhnya dalam Third Language Vocabulary Acquisition Bahasa Korea - Meidina R, Irvanti Sufa; Cahyono, Rudi (Universitas Airlangga, 2023)
This research is a preliminary study to see the effect of survival show program consumption on Korean language third language vocabulary acquisition. The study used a one-way pre-test post-test design with 10 participants (N=10) aged between 18 and 24 years old currently studying Korean autodidactly as their third language. The survival show program used in this experiment is the 5th episode of the show